(untitled) (Torani Journal of Fisheries and Marine Science, 2017)
The research aim was to compare inner mating of Penaeus monodon and to determine growth of junevile from cross mating between broodstock from the same and different area. This study was using broodstock from Siwa and Pangkep. Six broodstock from the same and different area would then been mating. Parameters for broodstock quality were measured including fecundity, period of mating, fertilization, egg diameter and egg hatching capability. Parameters for measuring larvae quality were survival rate, number of larvae for each stage, growth of larvae for each stage. The result showed that the best reproductive potency were fecundity, fertilization and survival rate of larvae that found from mating between female broodstock from Siwa and male broodstock from Pangkep. Keywords : Source of broodstock, Penaeus monodon, reproductive potency, broodstock and larvae quality